The Effect of Recombinant Anthrax Lethal Toxin on Breast Cancer Cell Motility, Adhesion, and Invasion - El Chami, Dana (2020)
Breast cancer-related deaths are mostly due to breast cancer invasion and migration to distant secondary regions. Targeting breast cancer cell metastasis is an important therapeutic approach. The mitogen-activated protein kinase (MAPK) pathway is a key cell signaling pathway that plays a major role in cell invasion and migration. Many studies have targeted the MAPK pathway as a way to target cell survival and motility. In this study, we use Lethal Toxin (LT) a potent MAPK inhibitor that selectively inactivates all the kinases in the MAPK pathway. LT proved to affect breast cancer cell migration, adhesion, and invasion. Cells treated with LT showed a significant decrease in motility as seen in 2D time-lapse and wound healing assays. Additionally, cells treated with LT showed an increase in adhesion, decrease in invasion across a collagen matrix, and in increase in Rho A activation. We speculate that LT inhibited cell migration by deregulating the activity of Rho GTPases, proteins known to play a role in cell migration. In this study, we describe the effect of LT as a potential breast cancer cell invasion and motility inhibitor.